Design and development of electrical powered wheelchair model for navigation control: article / Afiqah Yaacob - Yaacob, Afiqah
Manual wheelchair used to help the elderly and the handicapped for their mobility with assisted from other person. This paper presents a model of electrical powered wheelchair (EPW) which moves according to the motion mode ofajoystick operated by one person. The wheelchair model move when user moves the joystick according to any direction. The signal from joystick is converted to digital signal by Analogue to Digital Converter (ADC). This digital signal will enable the microcontroller to perform simple control algorithm to drive the DC motor to move forward or backward. The navigation also is aided by the sonar range sensor. The sensor will sense hole on pathway then automatically avoid the hole and alert the user from bazzer sound. The design of the system was compact and small thus suitable to be implemented into real wheelchair.